Spatial distribution and influencing factors of China’s overseas farmland investment projects under the background of food security - Yameng Wang; Fan Zou; Luning Wang; Huawang Jin; Linyan Ma (Frontiers in Sustainable Food Systems)
Since the 21st century, overseas farmland investment has gradually become the focus of research in the field of transnational agricultural investment. Under the background of China’s “going out” strategy, exploring the spatial distribution pattern and influencing factors of China’s overseas farmland investment activities in different regions of the world and reducing domestic food supply pressure through effective use of overseas farmland resources has become an important path for China to ensure food security. Based on the case data of China’s overseas cultivated Land investment in the Land Matrix database, this paper sorted out the utilization status of China’s global cultivated land resources, and analyzed the spatial distribution and influencing factors by using spatial analysis method and grey correlation analysis method. The results show that: (1) At present, the host countries of China’s overseas cultivated land investment have obvious spatial aggregation, showing the spatial characteristics of “small agglomeration and large dispersion,” and have the characteristics of distribution along the border and river; (2) China’s overseas farmland investment is affected by geo-economy, resource base, geo-culture and geopolitics, and the degree of impact is weakened in turn. Among them, the average annual import and export value, total water resources and other indicators have a significant impact on the investment choice of Chinese enterprises. Based on this, on the basis of identifying the spatial distribution pattern of China’s global overseas farmland investment and development and analyzing its key driving factors, this study proposed the path that overseas farmland investment and development can help improve the resilience of food system with the goal of ensuring the food security of sustainable agricultural system. It provides a theoretical basis for the country to formulate food security strategy based on overseas farmland investment and guide enterprises to invest overseas farmland.